1997
DOI: 10.1128/iai.65.9.3622-3630.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of adherence in interleukin-8 induction in Helicobacter pylori-associated gastritis

Abstract: Active Helicobacter pylori-associated gastritis is characterized by a dense mucosal infiltration with granulocytes. Since H. pylori is noninvasive, secondary signals must induce the accumulation of granulocytes. Interleukin-8 (IL-8) has been shown to play a key role in this event. Using competitive reverse transcriptase-PCR on mRNA from gastric biopsies, we could show a clear correlation between the amount of IL-8 transcripts and the activity of H. pylori gastritis. Due to the inability of the bacterium to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 56 publications
2
51
1
Order By: Relevance
“…Chemokine secretion was measured in supernatants by ELISA measurement. In agreement with previous studies [23] we found a strong IL-8 production by gastric epithelial cells in response to TNF-a . Fractions of H. pylori neither alone nor in combination with TNF-a and IFN-g stimulated IL-8 secretion.…”
Section: Effects Of Living H Pylori On Epithelial Il-8 Mig and Ip-1supporting
confidence: 93%
“…Chemokine secretion was measured in supernatants by ELISA measurement. In agreement with previous studies [23] we found a strong IL-8 production by gastric epithelial cells in response to TNF-a . Fractions of H. pylori neither alone nor in combination with TNF-a and IFN-g stimulated IL-8 secretion.…”
Section: Effects Of Living H Pylori On Epithelial Il-8 Mig and Ip-1supporting
confidence: 93%
“…Such adherence of live H. pylori to gastric epithelial cells is indispensable for the stimulation of IL-8 secretion. 17 Therefore, firm contact between H. pylori and the host cell by such adhesion is thought to be a prerequisite for the H. pylori to transport effecter molecules into the host cell using the cagPAI-encoded type IV secretion system, which is regarded as the pathway leading to the generation of IL-8 in the coculture system together with MKN45 and H. pylori. Lactobacilli have been reported to inhibit the adhesion of many kinds of pathogenic bacteria to epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that IL-8 production requires direct contact between H. pylori and epithelial cells. [34][35][36] Accordingly, gastric epithelial cells in culture produce IL-8 in the presence of viable H. pylori, but not when the bacterium is killed or is viable but separated from cells by a membrane or by H. pylori culture supernatant. 18,34 In addition, H. pylori induces protein tyrosine phosphorylation, which is involved in IL-8 production, in gastric epithelial cells.…”
mentioning
confidence: 99%